In vitro propagation and molecular characterization of somaclonal variation in Phalaenopsis gigantea - Samarfard, Samira (2013)
Phalaenopsis gigantea (Elephant‟s Ear orchid) is the largest species of Phalaenopsis genus originating from the lowland forests of Malaysia and Indonesia. Deforestation and over-collection have resulted in the extinction of this orchid. P. gigantea has the potential of producing beautiful hybrids and currently research on micropropagation using plant growth regulators of this orchid is ongoing. Chitosan is an environmentally friendly carbohydrate polymer and has been reported to stimulate growth of some plant species, including orchids. Multiplication was undertaken through in vitro inoculation of PLBs in liquid New Dogashima medium (NDM) and Vacin and Went (VW) medium supplemented with different concentrations of chitosan (0, 5, 10, 15, 20 and 25 mg/L) during 8 weeks of culture. The best response was established at 10 mg/L of chitosan supplementation in both media with the mean number of 177 and 147 PLBs formed on VW and NDM, respectively. After 6 weeks of culture in liquid media, some PLBs differentiated producing juvenile leaves and the best response was obtained on NDM at 20 mg/L chitosan with mean number of 66 leaves. To establish an efficient treatment combination in semi solid culture for enhancing PLBs multiplication and subsequent shoot regeneration, solid NDM and VW medium supplemented with various concentrations of chitosan (0, 5, 10, 15, 20 and 25 mg/L) and thidiazuron (TDZ) (0, 0.1, 0.5 mg/L) were used. The optimum treatment for PLB multiplication in solid medium was NDM at 10 mg/L chitosan in combination with 0.1 mg/L TDZ with the mean number of 353 PLBs after 20 weeks of cultivation. NDM containing 10 mg/L chitosan and 0.1 mg/L TDZshowed a 19-fold increase in fresh weight. Whilst, the efficiency of shoot regeneration in semi solid VW was higher than NDM and the best response was observed on VW in addition with 10 mg/L chitosan and 0.5 mg/L TDZ (16), VW at 20 mg/L chitosan (15) and VW including 15 mg/L chitosan and 0.5 mg/L TDZ (13). In order to assess the genetic fidelity among initial PLBs and proliferated PLBs obtained at the end of each two week's sub-culture from the optimum treatment (10 mg/L chitosan). Eight inter-simple sequence repeat (ISSR) primers were finally selected from 10 used for initial screening. The ISSR primers generated 55 clear band classes with 0% polymorphism. The somaclonal variations among mother plant (MP) and PLBs from the sub-cultures of optimum treatment in PLB multiplication (solid NDM supplemented with 10 mg/L chitosan and 0.1 mg/L TDZ) have been estimated. The primers selected produced 67 bands with 11 of it being polymorphic. The highest number of polymorphic bands (3) was obtained using primers I65 and I2 with 27.3% polymorphism. It was found that no genetic changes occurred among mother plant and PLBs after 4, 8 and 12 weeks of culture. After 16 and 20 weeks of culture, PLBs were 95% and 80% similar to MP, respectively. In summary, the present report expressed that the addition of 10 mg/L chitosan in liquid medium could provide a promising in vitro culture system to stimulate PLBs proliferation withoutany somaclonal variation up to 16 weeks of culture. The incorporation of 10 mg/L chitosan and 0.1 mg/L TDZ in solid NDM was also efficient for PLB proliferation. However, it resulted in 20% dissimilarity with the mother plant after 20 weeks of culture.